INVESTASI SDM MELALUI PENDIDIKAN DAN NILAI EKONOMI PENDIDIKAN - Chairul Furqon (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
As widely known, capable human resource holds an important role in the economicdevelopment. One among many other media for improving human resource capability is education and training in which human resource is facilitated to develop their knowledge, skills and attitude. At glance, education looks to be a cost. However, it actually is a long-term investment because the education process results in a better bargaining power of human resource before the corporate organizations requiring capable human resource. In addition, the result of the education process simultaneously contributes to the country’s economic growth. Capable human resource plays a part in improving social welfare as well. Better welfare theoretically corresponds to better purchasing power and unquestionably promotes the country’s economic development